Mechanical properties and interfacial characterization of additive-manufactured CuZrCr/CoCrMo multi-metals fabricated by powder bed fusion using pulsed wave laser - Zhang, Hao (2024)
In this study, CoCrMo cuboid samples were deposited on a CuZrCr substrate using laser powder bed fusion (L-PBF) technology to investigate the influence of process parameters and laser remelting strategies on the mechanical properties and interface characteristics of multi-metals. This study found that process parameters and laser scanning strategies had a significant influence on the mechanical properties and interface characteristics. Samples fabricated with an EV ≤ 20 J/mm3 showed little tensile ductility. As the volumetric energy density (EV) increased to a range between 40 J/mm3 and 100 J/mm3, the samples achieved the desired mechanical properties, with a strong interface combining the alloys. However, an excessive energy density could result in cracks due to thermal stress. Laser remelting significantly improved the interface properties, especially when the EV was below 40 J/mm3. Variances in the EV showed little influence on the hardness at the CuZrCr end, while the hardness at the interface and the CoCrMo end showed an increasing and decreasing trend with an increase in the EV, respectively. Interface characterization showed that when the EV was greater than 43 J/mm3, the main defects in the L-PBF CoCrMo samples were thermal cracks, which gradually changed to pores with a lack of fusion when the EV decreased. This study provides theoretical and technical support for the manufacturing of multi-metal parts using L-PBF technology.